Book Review: Michael Belgrave, Merata Kawharu and David Williams (eds) Waitangi Revisited: Perspectives on the Treaty of Waitangi - Northover, Hannah (Victoria University of Wellington Law Review, 2005)
This article is a book review of Michael Belgrave, Merata Kawharu and David Williams (eds) Waitangi Revisited: Perspectives on the Treaty of Waitangi (Oxford University Press, Melbourne, 2005) (402 + xxi pages) NZ65. The book looks at issues surrounding the Treaty of Waitangi 16 years after the publication of "Waitangi: Māori and Pākehā Perspectives of the Treaty of Waitangi". Although it can be difficult to find cogent and lucid expressions of contrary opinions on Treaty issues, Northover states that the book’s attempts to provide different ideological perspectives are relatively successful. Other pieces are more akin to case studies, illustrating wider schemes and issues of significance. It is concluded that the book deserves to be read by a wide audience, and that the contributions in the collection reflect Treaty issues that remain (and will remain) prominent.